DFT study of trialkylborohydride-catalysed hydrosilylation of alkenes – the mechanism and its implications. Issue 4 (20th January 2020) - Nowicki, Mateusz; Zaranek, Maciej; Pawluć, Piotr; Hoffmann, Marcin
Abstract : A detailed DFT study reveals the mechanism of trialkylborohydride-catalysed Markovnikov hydrosilylation of aromatic alkenes. Abstract : Here we present the results of our DFT study of triethylborohydride-catalysed CC bond hydrosilylation reactions. On the basis of the investigation of the potential energy hypersurface at the M06-2X/6-31++G(d, p)//M06-2X/6-31+G(d) level of theory, we propose a detailed mechanism and energy profile for the reaction of styrene with phenylsilane and describe geometric and electronic structures of stationary points corresponding to each step. The model proposed is also applied to a number of other potential reagents, namely 1, 1-diphenylethene, propene, dimethylphenylsilane, and trimethylsilane. The results of quantum-chemical computations not only provide a consistent explanation of the high regioselectivity of NaHBEt3 -catalysed hydrosilylation, but are also in good agreement with the experimental yields depending on the substrates used, hence they not only further support the mechanism presented, but also make a computational toolkit for predicting reactivities.